Total English starter - Bygrave, Jonathan; Pearson Education ([Harlow] : Pearson Education, 2007)
The grammar activities give a new ways to utilize the grammar points in each unit
Class CD1: DYK Recording 1-Unit 6 Recording 6 (77 min.) -- Class CD2: Unit 6 Recording 7-Unit 10 Tests A+B Unit 1-10 (80 min.)
Title from container
Keywords: English language -- Problems, exercises, etc; English language -- Study and teaching -- Foreign speakers